2012
DOI: 10.1001/archinternmed.2012.3138
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Weight Training and Risk of Type 2 Diabetes Mellitus in Men

Abstract: Background The role of weight training in the primary prevention of type 2 diabetes is largely unknown. We examined the association of weight training with risk of type 2 diabetes among U.S. men and assessed the influence of combining weight training and aerobic exercise. Methods We performed a prospective cohort study among 32,002 men from the Health Professionals Follow-up Study that were followed from 1990 until 2008. Weekly time spent on weight training and aerobic exercise (including brisk walking, jogg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
151
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(174 citation statements)
references
References 40 publications
(39 reference statements)
16
151
2
5
Order By: Relevance
“…Follow-up time varied from 3 [42] to 23.1 [60] years. Twelve studies were conducted in the USA [12,14,35,38,46,58,[60][61][62][63][64][65], six in Asia [47,57,59,[66][67][68], two in Australia [40,42] and eight across Europe [13,36,37,39,41,[69][70][71]. All cohorts relied on self-reported PA collected using questionnaires or by interview, apart from one study in Hawaiians [58].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up time varied from 3 [42] to 23.1 [60] years. Twelve studies were conducted in the USA [12,14,35,38,46,58,[60][61][62][63][64][65], six in Asia [47,57,59,[66][67][68], two in Australia [40,42] and eight across Europe [13,36,37,39,41,[69][70][71]. All cohorts relied on self-reported PA collected using questionnaires or by interview, apart from one study in Hawaiians [58].…”
Section: Resultsmentioning
confidence: 99%
“…In the context of type 2 diabetes, earlier studies have found that dose-response curves may be different for Asian Ding et al (2015) [42] Burchfiel et al (1995) [58] Magliano et al (2008) [40] Steinbrecher et al (I) (2012) [38] Grøntved et al (2012) [61] Demakakos et al (2010) [71] Haapanen et al (II) (1997) [36] Krishnan et al (2009) [64] Chien et al (2009) [68] Folsom et al (2000) [62] Carlsson et al (2007) [41] Ekelund et al (II) (2012) [39] Nakanishi et al ( 2004) [57] Steinbrecher et al (II) (2012) [38] Meisinger et al (II) (2005) [37] Okada et al (2000) [66] Grøntved et al (II) (2014) [35] Fretts et al (2009) [46] Lynch et al (1996) [13] Meisinger et al (I) (2005) [37] Haapanen et al (I) (1997) [36] Subtotal (I Indians who may require more PA to be protected from their relatively higher susceptibility to develop type 2 diabetes [72,73]. A potential strength of our present analyses is the expression of PA exposure dose in MMET h/week rather than just MET h/week.…”
Section: Discussionmentioning
confidence: 99%
“…One longitudinal study suggested that poor muscular strength (as quantified by a combination of leg and bench presses) is a risk factor for the metabolic syndrome [23]. Moreover, resistance exercise training has been shown to reduce the risk of developing diabetes mellitus [5,6]. Based on these results, poor TFS is considered to be a potential risk factor for diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced mass of skeletal muscle and reduced fitness are related to the prevalence of diabetes mellitus, impaired glucose tolerance, and insulin resistance [2][3][4]. In addition, resistance exercise training can reduce the risk of type-2 diabetes mellitus significantly independent of aerobic exercise training [5,6]. Therefore, the strength and mass of the muscle may have a role Submitted Dec. 6, 2017; Accepted Feb. 25, 2018 as EJ17-0517 Released online in J-STAGE as advance publication Mar.…”
mentioning
confidence: 99%
“…However, it is not known whether these PA guidelines are met by Korean adults. In general, meeting the recommended levels of PA is known to be beneficial in improving the general health and preventing chronic diseases [5,13,14]. To increase the proportion of Korean adults meeting the PA guidelines, it is important to identify the interrelationships or determinants of participation in PA.…”
Section: Discussionmentioning
confidence: 99%